Chorangiocarcinoma, doubloe tumor of the placenta - Pereda Garay, José (2015)
A case of chorioangioma of the placenta associated with an abnormal proliferation of the trophoblast, condition that has been called chorangiocarcinoma, is reported. This is the fifth report on the subject in the medical literature. The current case presented preeclampsia, angioma in the newborn and atypical proliferation of the endothelial cell, aspects not mentioned in previous reports.